Early pregnancy serum neopterin concentrations predict spontaneous preterm birth in asymptomatic pregnant women - Navolan, Dan Bogdan; Vladareanu, Simona; Lahdou, Imad; Ciohat, Ioana; Kleist, Christian; Grigoras, Dorin; Vladareanu, Radu; Terness, Peter; Sas, Ioan (Journal of perinatal medicine, 2016)
Abstract Objective: To investigate if early pregnancy serum neopterin concentrations (EPSN) could predict spontaneous preterm birth (SPB). Methods: EPSN was measured in 92 sera collected from 46 pregnant women with birth at term and 40 sera from 20 pregnant women with preterm birth. Two sera were collected for each case: in the first and early second trimester. Results: EPSN concentrations correlate with gestational age (ρ=0.275, P=0.001), a correlation which was present in both groups: term and preterm birth. EPSN were higher in pregnancies with SPB compared with normal pregnancies (6.27±1.03 vs. 6.04±0.15, P=0.039). Patients with SPB showed a considerable increase of EPSN in the second trimester compared with patients with birth at term (7.30±1.53 vs. 6.16±0.23, P=0.043). A sharper increase was found in the group with SPB before 32 weeks of pregnancy (wp) (9.83±4.36 vs. 6.16±0.23, P=0.016). Pregnant women with an early second trimester serum neopterin value of above 8 nmol/L are associated with a risk of SPB before 32 wp (odds ratio=14.4, P=0.01) and of SPB before 34 wp (odds ratio=3.6, P=0.05), respectively. Conclusions: EPSN increases with the gestational age and predicts SPB in asymptomatic pregnant women.
Published online 2015
Gesehen am 06.10.2020